KAJIAN LITERATUR TERHADAP METODE PENERIMAAN TEKNOLOGI: STUDI DALAM KONTEKS SISTEM INFORMASI DAN INOVASI DIGITAL - Muhammad Risyad Alfarabi; Besse Hartati; Cakra Trinata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digital transformation has driven various sectors, including immigration services, to adopt information technology in order to enhance service efficiency. This study employs a Systematic Literature Review (SLR) using the PRISMA framework to analyze the effectiveness of technology acceptance models—TAM, UTAUT, TRAM, and DeLone & McLean—within the context of public services. The findings reveal that TAM is the most frequently applied model (43%), followed by UTAUT (30%), TRAM (17%), and DeLone & McLean (7%). However, not all TAM variables significantly influence technology acceptance, and critical aspects such as government trust and data security are often overlooked. This study highlights gaps in existing models and recommends the development of a hybrid model that integrates TAM and UTAUT, incorporating these external factors to better suit public sector applications.